Power Spectral Analysis of a Forcemain Failure Caused By Waterhammer - Hennessy, Robert R. (My University, 1977)
﻿The failure of the Ancaster forcemain was thought to be related to waterhammer effects. The sequence of breakages of the main are reviewed. A series of pressure recordings were made on the forcemain, leading up to and including collapse. The recordings comprise a unique data set.
These pressure recordings were digitized and subjected to power spectral analysis. The power spectra pointed out several significant events that were not evident from the pressure record alone.
These included the fact that the original break occurred in the forcemain several days prior to its ultimate collapse and discovery on the surface. It was also determined that the break in the pipe was due to the apparent merging of the primary waterhammer wave with an existing but gradually changing lower frequency wave. This second wave was associated with rigid column motion and gradually increased its frequency. The resultant wave carried sufficient energy to cause the ultimate failure of the evidently already damaged forcemain.
Power spectral analysis proved useful as a method for analysing waterhammer effects in a forcemain complicated by column separation, leakage and vapour pocket collapse. and may be a useful way of monitoring the performance of longer pipelines.
Keywords: failure, forcemain, waterhammer, pressure, pipe, wave, power